Predictors of slow flow during primary percutaneous coronary intervention: an intravascular ultrasound-virtual histology study. Issue 12 (1st April 2008) - Bae, J H; Kwon, T-G; Hyun, D-W; Rihal, C S; Lerman, A
Abstract : Objectives: Slow flow phenomenon is a serious complication of percutaneous coronary intervention (PCI) and is associated with a poor prognosis. We sought to evaluate the characteristics of lesions predisposing to the slow/no-reflow phenomenon during primary PCI in patients with acute myocardial infarction. Methods: The study subjects consisted of 57 consecutive patients (mean age 58.5 (SD 14.5) years, 45 males) who underwent primary PCI for acute myocardial infarction and intravascular ultrasound-virtual histology (IVUS-VH) examination. Slow flow was defined as ⩽ thrombolysis in myocardial infarction grade 2 after PCI. Results: Slow flow developed in 12 patients (eight males). Patients with slow flow were likely to be older (67.5 (13.8) years vs 56.2 (13.9) years, p = 0.015), had more cardiogenic shock (16.7% vs 2.2%, p = 0.046), larger fibrofatty volume over the entire lesion length (36.7 (25.5) mm 3 vs 18.0 (18.6) mm 3, p = 0.006), higher remodelling index (1.10 (0.17) vs 0.99 (0.16), p = 0.043), larger plaque area (16.2 (5.4) mm 2 vs 12.5 (4.9) mm 2, p = 0.025), fibrous area (8.0 (3.3) mm 2 vs 5.4 (3.0) mm 2, p = 0.014) and fibrofatty area (2.7 (2.2) mm 2 vs 1.3 (1.6) mm 2, p = 0.016) at the minimal lumen site than those without slow flow (37 males). Multivariate analysis revealed that the fibrofatty volume over the entire lesion length was the only independent factor (β = 0.359, 95% confidence interval 0.002 to 0.012, p = 0.006) for slow flow during primary PCI. Conclusions: This study suggests that slow flow may be dependent on the tissue characterisation (fibrofatty volume) of the underlying lesion at the time of the primary PCI for acute myocardial infarction.